2019
DOI: 10.1111/cpr.12585
|View full text |Cite
|
Sign up to set email alerts
|

p62 functions as an oncogene in colorectal cancer through inhibiting apoptosis and promoting cell proliferation by interacting with the vitamin D receptor

Abstract: Objectives:The role of p62 in cancer is controversial. Evidence has shown that p62 is upregulated in different cancers and promotes tumour growth, such as in liver cancer and lung cancer. However, a recent study showed that the downregulation of p62 in hepatic stellate cells (HSCs) promotes hepatocellular carcinoma (HCC) development.How p62 is regulated in colorectal cancer (CRC) remains largely unknown. In this study, we aimed to investigate the roles and molecular mechanisms of p62 in CRC. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Valencia et al ( 44 ) also observed that the expression of p62 was declined in the stroma of several tumors, and as an anti-inflammatory tumor suppressor, p62 could inhibit tumor development by modulating the metabolism in the tumor stroma. In addition, low p62 expression is closely associated with poorer outcomes in patients with colorectal cancer, as patients with low p62 expression display the most aggressive tumor features ( 45 ). Thus, p62 is considered as a candidate for autophagy-modulating therapies to treat tumors ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Valencia et al ( 44 ) also observed that the expression of p62 was declined in the stroma of several tumors, and as an anti-inflammatory tumor suppressor, p62 could inhibit tumor development by modulating the metabolism in the tumor stroma. In addition, low p62 expression is closely associated with poorer outcomes in patients with colorectal cancer, as patients with low p62 expression display the most aggressive tumor features ( 45 ). Thus, p62 is considered as a candidate for autophagy-modulating therapies to treat tumors ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of in vivo and in vitro studies have reported that SQSTM1 can promote tumor development and malignant phenotypes such as tumor growth, invasion, migration and apoptosis inhibition via multiple signal transduction pathways (13,25,26). Previous studies have con rmed the double-edged sword effect of autophagy in regulating tumors which highlighted the importance of SQSTM1 expression pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary, overexpression of p62 enhances the resistance to this chemotherapeutic agent, preventing cell death in response to this treatment ( 77 ). In the colorectal cancer cell line SW480, p62 proteins levels are found elevated ( 78 ), which correlates with active autophagy pathway compared to other cellular models of this type of cancer ( 79 ). Interestingly, silencing of p62 in SW480 cell line decreases cell proliferation and their capacity to invade and migrate.…”
Section: Molecular Features Of Autophagy Cytosolic Receptorsmentioning
confidence: 95%
“…Interestingly, silencing of p62 in SW480 cell line decreases cell proliferation and their capacity to invade and migrate. Additionally, injection of p62 depleted SW480 cells in mice decreases tumor growth and metastasis into the lung, compared to control cells ( 78 ). Similar findings have been reported with F5M2 and F4 cell lines of osteosarcoma, which present high levels of p62 ( 73 ).…”
Section: Molecular Features Of Autophagy Cytosolic Receptorsmentioning
confidence: 99%